The Yusuf trilogy. [part 1], Yumurta [videorecording (DVD)] - Kaplanoğlu, Semih, 1963-; Isler, Nejat; Aksoy, Saadet Ișıl; Bayraktar, Ufuk (Olive Films, 2011)
Emotionally distant poet Yusuf returns home to settle his late mother's affairs. A young girl who's a distant relative awaits him in the crumbling house. Yusuf has been unaware of her existence and is surprised to find that she's been living with his mother for the past five years. Yusuf is now obliged to perform a sacrifice which had been his mother's dying wish.